Determinants of optimisation of Belarusian-Chinese intercultural communication in the context of globalisation - Basova, Anna I.; Rongyan, Tang (Journal of the Belarusian State University. Journalism, 2023)
In accordance with the problem-thematic principle, the material is systematised according to the degree of study of intercultural communication in the research community of Belarus and China. It is noted that the strengthening of relations between the two countries has led to the appearance in recent decades of works devoted to the study of Belarusian-Chinese intercultural communication in the fields of politics, science, culture, education, sports and tourism.